High Developmental Rates of Mouse Oocytes Cryopreserved by an Optimized Vitrification Protocol: The Effects of Cryoprotectants, Calcium and Cumulus Cells - KOHAYA, Natsuki; FUJIWARA, Katsuyoshi; ITO, Junya; KASHIWAZAKI, Naomi (Journal of Reproduction and Development, 2011)
Unfertilized oocytes are one of the most desired germ cell stages for cryopreservation because these cryopreserved oocytes can be used for assisted reproductive technologies, including in vitro fertilization (IVF) and intracytoplasmic sperm injection. However, in general, the fertility and developmental ability of cryopreserved oocytes are still low. The aim of the present study was to improve vitrification of mouse oocytes. First, the effects of calcium and cryoprotectants, dimethyl sulfoxide and ethylene glycol (EG), in vitrification medium on survival and developmental ability of vitrified oocytes were evaluated. Oocytes were vitrified by a minimal volume cooling procedure using different cryoprotectants. Most of the vitrified oocytes were morphologically normal after warming, but their fertility and development were low independently of calcium and cryoprotectants. Second, the effect of cumulus cells on ability of oocytes to be fertilized and develop in vitro was examined. The fertility and developmental ability of denuded oocytes (DOs) after IVF were reduced compared with cumulus-oocyte complexes (COCs) both in fresh and cryopreserved groups. Vitrified COCs showed significantly (P<0.05) higher fertility and ability to develop to the 2-cell and blastocyst stages than those of vitrified DOs with cumulus cells and vitrified DOs alone. The vitrified COCs developed to term at a high success rate equivalent to the rate obtained with IVF using fresh COCs. Taken together, the current results clearly demonstrate that, in the presence of surrounding cumulus cells, matured mouse oocytes vitrified using calcium-free media and EG retain their developmental competence. These findings will contribute to improve oocyte vitrification in not only experimental animals but also clinical application for human infertility.